2019
DOI: 10.1111/cote.12435
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated weathering performance of Scots pine preimpregnated with copper‐based chemicals before varnish coating Part:1 coated with cellulosic and polyurethane varnishes

Abstract: This study aimed to determine the effect of accelerated weathering on gloss, surface hardness and colour changes of Scots pine (Pinus sylvestris L.). Test samples were impregnated with Adolit KD‐5, Wolmanit CX‐8 and Celcure AC‐500 covered with cellulosic and polyurethane varnishes. The results showed that the values of surface hardness and gloss increased after accelerated weathering. While the surface hardness of Scots pine was increased for impregnated and polyurethane‐coated varnish, it decreased for impreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…According to the results, they found that the hardness values of the PV coated Scots pine increased with the impregnation process before weathering. While our results for WBV coated Calabrian pine are not similar to Gündüz et al (2019), our results for PV coated Calabrian pine are in good agreement with the data Gündüz et al (2020). According to our results, the hardness values of the PV coated Calabrian pine specimens were higher compared to the WBV coated Calabrian pine specimens before weathering.…”
Section: Surface Hardnesssupporting
confidence: 71%
See 1 more Smart Citation
“…According to the results, they found that the hardness values of the PV coated Scots pine increased with the impregnation process before weathering. While our results for WBV coated Calabrian pine are not similar to Gündüz et al (2019), our results for PV coated Calabrian pine are in good agreement with the data Gündüz et al (2020). According to our results, the hardness values of the PV coated Calabrian pine specimens were higher compared to the WBV coated Calabrian pine specimens before weathering.…”
Section: Surface Hardnesssupporting
confidence: 71%
“…They found that copper-based pre-impregnation before WBV coating resulted in a slight de-crease in the surface hardness of the Scots pine wood before accelerated weathering exposure. In another study, Gündüz et al (2020) studied the hardness values of the impregnated and PV coated Scots pine before accelerated weathering. According to the results, they found that the hardness values of the PV coated Scots pine increased with the impregnation process before weathering.…”
Section: Surface Hardnessmentioning
confidence: 99%
“…While the surface hardness of wooden material increases on impregnated and varnish-coated surfaces, a significant decrease in the hardness values of impregnated and varnish-coated test samples was observed due to the aging process in an accelerated ultraviolet environment (Gündüz et al 2020). What makes varnish UV resistant are usually the chemicals present in it.…”
Section: Fig 4 Effect Chart Of Chestnut Wood S/n Ratiosmentioning
confidence: 99%
“…But we know from practice that not always the entire surface of a wood product (e.g., floor, shelf, table) is exposed to light. Many scientific works deal with the change in wood colour [ 22 , 23 , 24 , 25 , 26 , 27 ] or the change of surface finishes on wood in the interior due to the influence of light [ 17 , 28 , 29 , 30 ] or after accelerated weathering [ 9 , 13 , 31 , 32 , 33 , 34 , 35 , 36 ]. However, the effect of visible light from short waves (violet-blue) and the thermic effect of the infrared components of natural light passing through window glass [ 36 , 37 , 38 ] have to be considered as indoor ageing factors [ 25 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%